Characterization and clonal distribution of four alleles of the speA gene encoding pyrogenic exotoxin A (scarlet fever toxin) in Streptococcus pyogenes (The Rockefeller University Press, 1991)
Streptococcus pyogenes strains producing pyrogenic exotoxin A (scarlet fever toxin) have recently caused episodes of streptococcal toxic-shock- like syndrome (TSLS). We exploited knowledge of genetic diversity and relationships among exotoxin A-producing patient strains provided by multilocus enzyme electrophoresis to select strains for comparative sequencing of toxin genes. Our analysis identified four alleles of speA in natural populations, one of which (speA1) occurs in many distinct clonal lineages and is probably old. Two other alleles (speA2 and speA3), characterized solely by single amino acid substitutions, were each identified in single clones that together have caused the majority of TSLS episodes. It is unlikely that these alleles have had a long association with S. pyogenes clones. A fourth allele (speA4) also is present in a single phylogenetic lineage and is 9% divergent from the other three toxin alleles. An absence of synonomous (silent) nucleotide changes in speA2 and speA3 is unusual and suggests that the allelic variation is not selectively neutral, which implies that the toxins are not functionally equivalent. These results may be important in helping to understand the recent increase in frequency and severity of disease caused by S. pyogenes.